Differences between male and female prostates in terms of physiology, sensitivity to chemicals and pathogenesis—A review in a rodent model - Sanches, Bruno D. A. [UNESP]; Carvalho, Hernandes F. [UNESP]; Maldarine, Juliana S. [UNESP]; Biancardi, Manoel F. [UNESP]; Santos, Fernanda C. A. [UNESP]; Vilamaior, Patricia S. L. [UNESP]; Taboga, Sebastião R. [UNESP] (Wiley, 2019)
The prostate is a gland that is not exclusively present in males, being also found in females of several mammalian species, including humans. There is evidence that the prostate in both sexes is affected by the same pathologies such as prostatitis, benign alterations and even cancer. In view of the difficulties of manipulating the prostate gland, the Mongolian gerbil (Meriones unguiculatus), a rodent species with high incidence of functional prostates in females, is widely used in studies of the female prostate. However, despite knowing much about the similarities between the female and male prostate, little emphasis has been placed on the differences between them. This review investigates the intersex differences in prostate development, physiology and pathogenesis. The female prostate develops earlier than in males and studies indicate that it is more sensitive to oestrogens than the male prostate, as well as being more sensitive to exposure to xenoestrogens, such as Bisphenol A and methylparaben, with a higher susceptibility to benign lesions in the adult and senile prostate than in males. In addition, the female prostate is impacted by pregnancy and the oestrous cycle, and is also dependent on progesterone. The peculiarities of the female prostate raise concerns about the risk of it undergoing neglected changes as a result of environmental chemicals, since safe dosages are established exclusively for the male prostate.
Keywords: BPA; ethinyloestradiol; female prostate; methylparaben; progesterone; sex differences